Utilizing stable water isotopes (δ2H and δ18O) to study soil-water origin in sloped vineyard: first results (Rudarsko-geološko-naftni zbornik, 2022)
The diversity of processes taking place in hillslope agro-ecosystems makes the estimation of vadose zone dynamics rather challenging. This paper presents the first insight into the research of volumetric water content, granulometric composition, meteorological data, precipitation and soil-water isotopic composition conducted within the SUPREHILL project at its vadose zone observatory. The main goals of this research are related to the evaluation of soil-water origin at the hillslope vineyard, but also to the estimation of depths until which precipitation infiltrates and where the occurrence of preferential flow is possible. For that purpose, hydrometeorological data, granulometric composition and stable isotopesof hydrogen (δ2H) and oxygen (δ18O) from precipitation and sampled soil water have been used. The results indicate the existence of a different isotopic signature in soil water, which suggests different infiltration patterns in the investigated area. Also, the results point out that surface runoff, subsurface runoff, and most of the passive wick lysimeters respond to precipitation, while the response of suction probes located at deeper depth is not that evident. This corresponds to the results related to the variation of water content at different depths. All the results indicate the possible existence of a low permeable layer at an approximate depth of 60 cm. Furthermore, preferential flow, if it exists, can be expected from the shallowest depths of the vineyard to a maximum depth of 80 cm. It is expected that an established long-term monitoring network at the SUPREHILL Observatory will give a more precise definition of soil-water behaviour and the existence of preferential flow.